Needs assessment survey for enhancing United States child agricultural injury prevention capacity: Brief report - Salzwedel, Marsha; Weichelt, Bryan P.; Burke, Rick; Lee, Barbara C. (Frontiers in Public Health, 2023)
The dissemination of childhood agricultural safety and health information and resources through organizations that farmers trust enhances implementation and the Socio-Ecological Model can help identify these organizations. However, to become effective partners in improving agricultural health and safety, organizations need to build capacity in child agricultural safety and health, thus, more information is needed about these organizations’ current practices, needs, and capacity for leadership, policy makers, and knowledge mobilization. An online survey was administered to organization leaders with an interest in child agricultural injury prevention, chosen through agricultural health and safety organization membership lists. Invitations to participate in the online survey were mailed to 95 organization leaders with three weekly reminders, resulting in participation from 50 organization leaders (53% response rate). Respondents indicated a high level of awareness of child agricultural injuries, yet few were actively engaged in injury prevention. When asked about “needs” for building capacity in injury prevention, over half (56%) identified a need for more promotion and dissemination of safety resources and strategies, including ATV safety, no extra riders on equipment, and keeping young children out of the worksite. The only topic that more than half of the organizations (54%) identified as “needing more information” was childhood agricultural injury surveillance. This assessment yielded valuable details for identifying opportunities, priorities, and topics for future collaborations and capacity building. Findings help inform national and international planning committees’ work, such as the next iteration of a US National Action Plan for Childhood Agricultural Injury Prevention, scheduled for release in 2024.